1997
DOI: 10.1212/wnl.48.5.1403
|View full text |Cite
|
Sign up to set email alerts
|

Familial schizencephaly associated with EMX2 mutation

Abstract: We describe two brothers aged 8 and 10 affected by severe bilateral schizencephaly, carrying an identical point mutation of the homeobox gene EMX2. Both children had severe neurologic deficits and mental retardation, although they differed in the anatomic extent of the brain malformation and in the severity of the clinical picture. The present findings, together with the reported cases of schizencephaly associated with EMX2 mutations, support the hypothesis that, at least in some cases, schizencephalies are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 0 publications
1
78
0
6
Order By: Relevance
“…Alterations of Wnt pathway signaling have been described within human cortical resections containing focal intra-cortical dysplasias, but the presence of heterotopias was not addressed in this study (Cotter et al, 1999). Loss-of-function mutations in EMX2 have been described in individuals with the radiological diagnosis of schizencephaly, a rare cortical dysplasia syndrome (Brunelli et al, 1996;Faiella et al, 1997;Granata et al, 1997). However, further work will be required to determine whether EMX2 loss in these individuals is associated with heterotopias or MZ/SP abnormalities as the neuroimaging techniques used to identify the individuals lacked the resolution to detect such microscopic lesions and the neuropathological findings in these cases have not been described.…”
Section: Emx2 -/-Mice Comprise a Novel Mouse Model Of Human Heterotopiasmentioning
confidence: 75%
“…Alterations of Wnt pathway signaling have been described within human cortical resections containing focal intra-cortical dysplasias, but the presence of heterotopias was not addressed in this study (Cotter et al, 1999). Loss-of-function mutations in EMX2 have been described in individuals with the radiological diagnosis of schizencephaly, a rare cortical dysplasia syndrome (Brunelli et al, 1996;Faiella et al, 1997;Granata et al, 1997). However, further work will be required to determine whether EMX2 loss in these individuals is associated with heterotopias or MZ/SP abnormalities as the neuroimaging techniques used to identify the individuals lacked the resolution to detect such microscopic lesions and the neuropathological findings in these cases have not been described.…”
Section: Emx2 -/-Mice Comprise a Novel Mouse Model Of Human Heterotopiasmentioning
confidence: 75%
“…Familial cases have been reported, suggesting a possible genetic origin within a group of neuronal migration disorders (Guerrini & Carrozzo, 2001). Recent studies have linked schizencephaly with a mutated gene called EMX2 homeobox gene (Guerrini & Carrozzo, 2001;Granata et al, 1997). If the gene EMX-2 is missing or defective, nerve cell growth and migration will not occur normally and lead to the formation of the clefts associated with schizencephaly.…”
Section: Schizencephalymentioning
confidence: 99%
“…Dubey et al (7) have reported the cardinal characteristics of schizencephaly: a hemispheric cleft delimited by an usually bilateral ependymal-pial sheath in the perisylvian region; a cleft lined by gray-matter linking the subarachnoid space with the ependyma of the lateral ventricle, and the association with multiple intracranial anomalies such as polymicrogyria, heterotopias, absence of pellucid septum, optic nerve hyperplasia and corpus callosum agenesia. The majority of cases described are of a sporadic nature, although there are reports on familial cases (3,6,11) . Some authors (2,3,6) have described homeotic gene EMX2 (Empty Spiracles, Drosophila, 2, Homolog of) mutations in patients with schizencephaly.…”
Section: Schizencephalymentioning
confidence: 99%